An assessment of mental health policy in Ghana, South Africa, Uganda and Zambia - Mwanza Jason; Ssbunnya Joshua; Ofori-Atta Angela; Kleintjes Sharon; Funk Michelle; Faydi Edwige; Kim Caroline; Flisher Alan (BMC, 2011)
Abstract Background Approximately half of the countries in the African Region had a mental health policy by 2005, but little is known about quality of mental health policies in Africa and globally. This paper reports the results of an assessment of the mental health policies of Ghana, South Africa, Uganda and Zambia. Methods The WHO Mental Health Policy Checklist was used to evaluate the most current mental health policy in each country. Assessments were completed and reviewed by a specially constituted national committee as well as an independent WHO team. Results of each country evaluation were discussed until consensus was reached. Results All four policies received a high level mandate. Each policy addressed community-based services, the integration of mental health into general health care, promotion of mental health and rehabilitation. Prevention was addressed in the South African and Ugandan policies only. Use of evidence for policy development varied considerably. Consultations were mainly held with the mental health sector. Only the Zambian policy presented a clear vision, while three of four countries spelt out values and principles, the need to establish a coordinating body for mental health, and to protect the human rights of people with mental health problems. None included all the basic elements of a policy, nor specified sources and levels of funding for implementation. Deinstitutionalisation and the provision of essential psychotropic medicines were insufficiently addressed. Advocacy, empowerment of users and families and intersectoral collaboration were inadequately addressed. Only Uganda sufficiently outlined a mental health information system, research and evaluation, while only Ghana comprehensively addressed human resources and training requirements. No country had an accompanying strategic mental health plan to allow the development and implementation of concrete strategies and activities. Conclusions Six gaps which could impact on the policies' effect on countries' mental health systems were: lack of internal consistency of structure and content of policies, superficiality of key international concepts, lack of evidence on which to base policy directions, inadequate political support, poor integration of mental health policies within the overall national policy and legislative framework, and lack of financial specificity. Three strategies to address these concerns emerged, namely strengthening capacity of key stakeholders in public (mental) health and policy development, creation of a culture of inclusive and dynamic policy development, and coordinated action to optimize use of available resources.